Efficient Broadband Upconversion of Near‐Infrared Light in Dye‐Sensitized Core/Shell Nanocrystals. Issue 11 (16th August 2016) - Chen, Guanying; Shao, Wei; Valiev, Rashid R.; Ohulchanskyy, Tymish Y.; He, Guang S.; Ågren, Hans; Prasad, Paras N.
Abstract : Efficient broadband upconversion of near‐infrared light is realized through multidimensional energy cascaded upconversion in dye‐sensitized core/shell nanocrystals. The upconversion energy conversion efficiency reaches as high as 16.4%.